THE RELATIONSHIP BETWEEN RETURN ON EQUITY, CURRENT RATIO, AND DEBT TO EQUITY RATIO ON STOCK PRICE WITH PRICE EARNING RATIO AS A MODERATING VARIABLE IN TELECOMMUNICATION SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2020 – 2023 - Rizky, Devano Alfa; Amelia, Dhea; Budianto, Erwin (Universitas Nusa Cendana, 2025)
While accounting for the price-earnings ratio, this study aims to isolate the effect of debt-to-equity, return-on-equity, and current ratios on stock prices. From 2020 to 2023, nine companies that were listed on the Indonesia Stock Exchange were selected for this study using a sample approach. The data was analyzed quantitatively using a variety of approaches in SPSS 23, including multiple linear regression and moderation regression analysis. Aside from the current ratio, the results show that no other variable significantly affects stock price. Furthermore, the ratio of debt to equity to stock price is moderated by the ratio of stock price to net income. Keywords: Return On Equity; Current Ratio; Debt to Equity Ratio; Price Earning Ratio